KEANEKARAGAMAN DAN KETIDAKNORMALAN MORFOLOGI PADA KOMUNITAS KOPEPODA (KRUSTASEA) DI PERAIRAN MUARA ANGKE DAN TANJUNG PASIR, TELUK JAKARTA - Mulyadi Mulyadi; Rena Tri Hernawati (BERITA BIOLOGI, 2022)
An observation on Copepoda diversity, abundance, and distribution in two mangrove areas in Jakarta Bay was carried out in May-June and September-October 2011. The objective of this observation was to investigate the relationship between diversity and abundance of copepods with some environmental factors which affected the distribution on dry and rainy seasons. A total 47 species from 26 genera, 20 families and 6 orders of copepods were recorded, including 3 new species, Calanopia asymmetrica Mulyadi & Ueda, 1996; Labidocera javaensis Mulyadi, 1997, and Pontella vervoorti Mulyadi, 2003, and 10 new records. The highest species richness occurred in the rainy season in Tanjung Pasir with 35 species, but the diversity index was very visible in Muara Angke, where during the rainy season the dominance index was high (0.2074), while the dry season had a high diversity index (Simpson 0.9481 and Shannon 3,279). Morphological abnormalities were found in the anal segment of the abdomen.